2016
DOI: 10.1007/s13205-016-0517-4
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of polygalacturonase from Aspergillus fumigatus MTCC 2584 and elucidating its application in retting of Crotalaria juncea fiber

Abstract: Polygalacturonases represents an important member of pectinases group of enzymes with diverse industrial applications and is widely distributed among fungi, bacteria, yeasts, plants and some plant parasitic nematodes. An endo-polygalacturonase from a new fungal source Aspergillus fumigatus MTCC 2584 was produced under solid-state fermentation conditions and was purified simply by acetone precipitation and gel-filtration chromatography technique. The approximate molecular weight of the purified PG was found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 38 publications
0
20
0
1
Order By: Relevance
“…However, pH stability range of the enzyme was wider (3.0-11.0) as compared to fungal PGs reported from A. niger (Kant et al 2013). An endo-PG with stability in alkaline range 7.0-11.0 has recently been reported from A. fumigatus (Anand et al 2016). …”
Section: Effect Of Ph On the Activity And Stability Of Pgmentioning
confidence: 98%
See 1 more Smart Citation
“…However, pH stability range of the enzyme was wider (3.0-11.0) as compared to fungal PGs reported from A. niger (Kant et al 2013). An endo-PG with stability in alkaline range 7.0-11.0 has recently been reported from A. fumigatus (Anand et al 2016). …”
Section: Effect Of Ph On the Activity And Stability Of Pgmentioning
confidence: 98%
“…It has been reported that activity of an acidic endo-PG from A. niger and alkaline endo-PG from A. fumigatus is enhanced by Cu 2? at 1 mM concentration (Zhou et al 2015;Anand et al 2016). Metal ions like Mn 2?…”
Section: Effect Of Metal Ions and Protein Inhibitorsmentioning
confidence: 99%
“…It appears that many endo-polygalacturonases belonged to acidic ones with optimal pH values around 3.5-6.0, including endo-TePG28b (pH 3.5) [23], endo-PGA1 (pH 3.5) [21], endo-PG I (pH 3.5) [18], Nfpg II (pH 4.0) [20], PGA-ZJ5A from Aspergillus niger ZJ5 (pH 4.5) [12], PG7fn (pH 5.0) [24], AaEPG (pH 5.0) [15], Nfpg I (pH 5.0) [20], endo-PG I (pH 6.0) [22], and PG2 (pH 6.0) [19]. Only several endo-polygalacturonases were classified as alkaline, such as Endo-PG from Aspergillus fumigatus MTCC 2584 with optimal pH 10.0 [35]. As shown in Figure 2, AnEPG showed the highest activity at pH 4.0, and no obvious activities were detected above pH 6.0.…”
Section: Determination Of Ph Optima and Ph Stability Of Anepgmentioning
confidence: 99%
“…Only several endo-polygalacturonases were classified as alkaline, such as Endo-PG from Aspergillus fumigatus MTCC 2584 with optimal pH 10.0 [35]. The pH stability of AnEPG was also investigated ( Figure 3).…”
Section: Determination Of Ph Optima and Ph Stability Of Anepgmentioning
confidence: 99%
“…It has been reported in the literature that Ca 2+ inhibits the catalytic action of polygalacturonase (Anand, Yadav, & Yadav, ). The present results also showed that Ca 2+ inhibited the catalytic ability of PgaB.…”
Section: Resultsmentioning
confidence: 99%